National socialism : basis principles, their application by the Nazi Party's foreign organization, and the use of Germans abroad for Nazi aims - Murphy, Raymond E. (Washington : United States Government Printing Office, 1943)
Bibliotheek Camille Huysmans
Engels
Monografie
Keywords: nationaalsocialisme; Nazisme; Wereldoorlog 2